Design and development of psychomotor assessment framework in open distance learning for hospitality education - Zamri @ Zimri, Mohd Taufik (2024)
This study explores the critical need for effective psychomotor assessments in hospitality education delivered through open distance learning (ODL), particularly in response to the rapid transition from face-to-face to ODL during COVID-19. The unique nature of psychomotor skills, which typically require hands-on practice, poses significant challenges in ODL environments, and there is a notable gap in how Malaysian higher education institutions (HEIs) have adapted these assessments. Motivated by the lack of empirical evidence and limited guidance on conducting psychomotor assessments in ODL for hospitality programs, this research aims to develop an adaptive framework aligned with 21st-century learning and technology integration. Using a Design and Development Research (DDR) methodology guided by the ADDIE instructional design model, the study proceeded through three phases. Phase I involved needs analysis via semi-structured interviews with nine hospitality educators, six students, and document analysis of five hospitality practical courses, with findings analyzed through reflexive thematic analysis. In Phase II, expert consensus was achieved through the Fuzzy Delphi Method (FDM), resulting in the development of 39 constructs and 308 items, refined into a final set of 34 constructs and 273 items. Phase III validated these frameworks through expert review. The research concluded in the development of two sequentially dependent frameworks: the Ecosystem of ODL Psychomotor Assessment, addressing critical components such as quality assurance, ODL standards, and leadership; and the Adaptive Formative and Summative ODL Psychomotor Assessment, which focuses on designing flexible and technology-integrated assessments. These frameworks provide concrete guidelines and best practices for improving the quality and adaptability of psychomotor assessments in ODL environments, benefiting hospitality education by ensuring more reliable and valid assessments of students' practical skills in a remote learning context.